The Influence Of Socıo-Demographıc Factors On Organizational Alienation Of Accommodation Businesses Employees - Unguren, Engin; Kacmaz, Yasar Yigit; Yilmaz, Yusuf (European Scientific Journal, ESJ, 2016)
In this study, the concept of alienation is analyzed in terms of organizational behavior discipline frame. As part of organizational behavior discipline, alienation is expressed as the server’s losing control over the product he produces or the service or inability of self-expression in business life. Basically, the concept of alienation is used to express alienation from the institution, occupation his own being, his valves, and society; in one sense it means a breakdown in all relations. The science of statistics plays an important role to identify the variable or variables effect the event in scientific studies and to determine their grades. Analysis of CHAID firms sub-sets by grouping the factors affecting the dependent variable in view of their importance level. In this term, the purpose of the research is to form to identify the employees’ organizational alienation level; demographic variables combined categories and sub-sets, working in accommodation services by using CHAID analysis technique.